2000
DOI: 10.1080/003655200451162
|View full text |Cite
|
Sign up to set email alerts
|

Fructose- and Sorbitol-reduced Diet Improves Mood and Gastrointestinal Disturbances in Fructose Malabsorbers

Abstract: -and sorbitol-reduced diet improves mood and gastrointestinal disturbances in fructose malabsorbers. Scand J Gastroenterol 2000; 35:1048-1052.Background: Fructose malabsorption is characterized by the inability to absorb fructose efficiently. As a consequence fructose reaches the colon where it is broken down by bacteria to short fatty acids, CO 2 and H 2 . Bloating, cramps, osmotic diarrhea and other symptoms of irritable bowel syndrome are the consequences and can be seen in about 50% of fructose malabsorber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(20 citation statements)
references
References 21 publications
3
14
0
3
Order By: Relevance
“…The result was believed to be associated with increased fermentation of carbohydrates [40]. In support of this study, fructose elimination diet was found to improve symptoms of depression as well as gastrointestinal symptoms [41]. Likewise, probiotics could also alleviate the depression-like behaviors in adult mice [42].…”
Section: Discussionsupporting
confidence: 57%
“…The result was believed to be associated with increased fermentation of carbohydrates [40]. In support of this study, fructose elimination diet was found to improve symptoms of depression as well as gastrointestinal symptoms [41]. Likewise, probiotics could also alleviate the depression-like behaviors in adult mice [42].…”
Section: Discussionsupporting
confidence: 57%
“…Although these results are promising, the latter two studies do not characterize the fructose content of the diet, either before or after instruction. In one of the few articles to report baseline dietary fructose intake, Ledochowski et al (2000) showed that fructose malabsorption was defined by an increase of 20 ppm of hydrogen over baseline following provision of a 50 g fructose load. Based on a dietary questionnaire, the mean daily total fructose intake of malabsorbing subjects was 20 g prior to the intervention and 5 g after dietary instruction to reduce both fructose and sorbitol intake.…”
Section: Resultsmentioning
confidence: 99%
“…The symptoms of fructose malabsorption (which may affect approx. 30% of the European population) for instance are characterized by the inability to absorb fructose in the small intestine leading to bloating, cramps, osmotic diarrhea and other symptoms of irritable bowel syndrome which can be seen in about 50% of fructose malabsorbers [2]. Low serum tryptophan and signs of folic acid and/or zinc deficiency can also be linked with the inability to absorb fructose efficiently [3].…”
Section: Introductionmentioning
confidence: 99%